2017
DOI: 10.15207/jkcs.2017.8.2.137
|View full text |Cite
|
Sign up to set email alerts
|

The Study on Cardiopulmonary Resuscitation(CPR) Willingness to Perform and Confidence according to Converged Job Experience of School Health Teacher

Abstract: .994, p=.025), the working school system(p=.000), teaching experience career(.003), number of educated CPR (p=.000), if you meet someone who meets cardiac arrest(p=.036).•

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The average knowledge score increased from 4.55 before CPR education to 5.01 (out of a total score of 8). Previous research has also reported greater knowledge after CPR education [25][26][27][30][31][32]. Therefore, early introduction of CPR education is needed [20,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average knowledge score increased from 4.55 before CPR education to 5.01 (out of a total score of 8). Previous research has also reported greater knowledge after CPR education [25][26][27][30][31][32]. Therefore, early introduction of CPR education is needed [20,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Confidence referred to confidence in one's ability to perform CPR, and the questionnaire was developed by Park [26]. In this study, confidence consisted of four questions, and the answer to each question was evaluated as "yes" (1 point) and "no" (0 points).…”
Section: Confidence In Performing Cprmentioning
confidence: 99%